1988
DOI: 10.1200/jco.1988.6.3.425
|View full text |Cite
|
Sign up to set email alerts
|

COPBLAM III: infusional combination chemotherapy for diffuse large-cell lymphoma.

Abstract: COPBLAM III, a polychemotherapy regimen consisting of cyclophosphamide, infusional vincristine, prednisone, infusional bleomycin, doxorubicin, and procarbazine, was administered to 51 patients with diffuse large-cell lymphoma. Ninety-six percent of patients age 60 or younger achieved a complete response (CR); none have relapsed. Overall, 88% of patients are alive and well and potentially in the survival plateau. For patients greater than 60 years, CR was obtained in 73%, with 42% potentially in the survival pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Use of the first-generation regimens such as CHOPb resulted in CR rates of approximately 45-50% and longterm survival of less than 30% (157). More aggressive second-and third-generation regimens, such as ProMACE-MOPP and COP-BLAM Illc, have further improved results with CR rates of 76% and 84% and long-term survival of 52% and 65%, respectively (158,159). Autologous bone marrow transplantation may be considered in patients with a second remission, and even as initial therapy in patients with poor prognostic features (160).…”
Section: Haematological and Biochemical Abnor-malitiesmentioning
confidence: 99%
“…Use of the first-generation regimens such as CHOPb resulted in CR rates of approximately 45-50% and longterm survival of less than 30% (157). More aggressive second-and third-generation regimens, such as ProMACE-MOPP and COP-BLAM Illc, have further improved results with CR rates of 76% and 84% and long-term survival of 52% and 65%, respectively (158,159). Autologous bone marrow transplantation may be considered in patients with a second remission, and even as initial therapy in patients with poor prognostic features (160).…”
Section: Haematological and Biochemical Abnor-malitiesmentioning
confidence: 99%
“…In the CHOP sequential trials at SWOG age had a powerful effect on CR and survival rates (Dixon et al, 1986). In the COP-BLAM 3 and COP-BLAM 4 trials, where patients had at age distribution closer to SNLG experience, age had an important effect on CR rates or durability (Boyd et al, 1988;Coleman et al, 1988). Shipp, who also noted fitness as an important determinant of response and survival, drew attention to the well recognised importance of fitness in prognosis of solid tumours, and the lack of data concerning fitness as a prognostic factor in NHL (Shipp et al, 1986).…”
mentioning
confidence: 99%
“…Optimistic reviews of NHL therapy have summarised the apparent progress due to the application of increasingly complex chemotherapy DeVita et al, 1988). ProMACE-MOPP, ProMACE-CytaBOM, M-BACOD, m-BACOD, COP-BLAM and its refinements, and MACOP-B are all contemporary variations on this theme 80 ll lll (Fisher et al, 1983;Fisher et al, 1987;Skarin et al, 1983;Canellos et al, 1987;Laurence et al, 1982;Boyd et al, 1988;Klimo & Connors, 1987). However response and survival 60 15 XL were significantly related to several patient and disease characteristics (Fisher et al, 1977;Cabanillas et al, 1978;Lenhard et al, 1978;Stein et al, 1979;Fisher et al, 1981;Armitage et al, 1982;Trump & Mann, 1982;Leonard et al, 40 1983;Sullivan et al, 1983;Al-Katib et al, 1984;Steward et al, 1984;Horning et al, 1984).…”
mentioning
confidence: 99%
“…Several studies have found a poorer prognosis of unfavourable NHL in elderly patients when compared to their younger counterparts (Jagannath et al, 1985;Solal-Celigny et al, 1987;Fisher et al, 1987;Dixon et al, 1986). Among other causes, such a difference of response may be related to less intensive treatment due to initial dose reductions of the drugs administered to elderly patients (Boyd et al, 1988). Therefore it may be expected that full dose chemotherapy given on schedule will lead to better complete response rates in elderly patients, provided that the toxicity of such an approach is acceptable (O'Connell et al, 1986;Dixon et al, 1986).…”
Section: Discussionmentioning
confidence: 99%